(untitled) (Journal of Fiber Bioengineering and Informatics, 2009)
Puerarin particles were prepared in the process of solution-enhanced dispersion by supercritical CO_2 (SEDS), where the dichloromethane was employed as an organic non-solvent to increase the saturation ratio of the initial puerarin solution in ethanol. A 2^3 factorial experiment was designed to investigate and identify the relative significance of the processing parameters on the yield of puerarin. In the range of the parameters studied, the yield increased with an increasing non-solvent/solvent ratio, and decreasing puerarin concentration or flow rate. The anti-oxidative activities of puerarin prepared under different parameters were also investigated, and the results show that there is no significant difference. The results indicate that the SEDS process combined with non-solvent could produce puerarin nanoparticles with a higher yield.